Economics of animal genetic resources use and conservation - Drucker, Adam G.; Ayalew, W.; Zander, K.K. (Food and Agriculture Organization of the United Nations, 2015)
Economic analysis can play an important role in the sustainable management of animal genetic resources (AnGR). The first report on The State of the World’s Animal Genetic Resources for Food and Agriculture (first SoW-AnGR) (FAO, 2007a) included a section on methods for economic evaluation 1 that provided an overview of the various types of value that can be distinguished (direct and indirect use values, option values, bequest values and existence values) and described potential methods and tools for assessing them. It also presented some examples of the use of these methods and tools and the findings obtained. This updated section provides an overview of recent developments in the economics of AnGR use and conservation. The revised title reflects the way in which this field of work has moved beyond just the development and testing of methods.